Analisis Pertumbuhan Ekonomi Pra, Saat, dan Pasca Pandemi di Provinsi Nusa Tenggara Timur Menggunakan Analisis Regresi Data Panel - Safaat Yulianto; Elisabeth Jeany Juanita Boisala; Zakaria Bani Ikhtiyar (Square : Journal of Mathematics and Mathematics Education, 2025)
Economic growth serves as a key factor in analyzing the economic conditions of a country or region. The secondary panel data used in this study consists of a combination of cross-sectional data from five regencies/cities in East Nusa Tenggara (NTT) that were most affected by the COVID-19 pandemic. This time-series data spans from 2018 to 2023 and is split into three phases: the period before the pandemic, the pandemic period, and the post-pandemic period.This study aims to analyze the factors influencing economic growth in NTT Province during the pre-, during-, and the period after the pandemic. The research employs the Fixed Effect Model (FEM) with Gross Regional Domestic Product (GRDP) as the dependent variable. The independent variables include the Regional Minimum Wage (UMR), Per Capita Expenditure, Labor Force Participation Rate (TPAK), and Domestic Investment (PMDN). The research findings indicate that the variables that significantly influence economic growth in NTT Province are the Regional Minimum Wage and Per Capita Expenditure. The Regional Minimum Wage has a negative impact on economic growth, whereas Per Capita Expenditure has a positive impact. This means that an increase in the Regional Minimum Wage will decrease economic growth, while an increase in Per Capita Expenditure will enhance economic growth.